Strategi Adaptasi Pemasaran Digital Produk Olahan Peternakan di Era Industri 4.0: Sebuah Tinjauan Literatur Sistematis (Systematic Literature Review) - Rais Mughni Salam; Asep Saeppani; Fadhil Irfan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Digital transformation in the era of Industry 4.0 has forced the livestock sector, particularly processed product SMEs (UMKM), to adapt their marketing strategies. Conventional marketing methods are increasingly limited by geographical boundaries and high operational costs. This study aims to identify and analyze the most effective digital marketing adaptation strategies for processed livestock products using a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar (2020–2025) using the PRISMA method. The results indicate that the most dominant strategies are the utilization of Social Commerce (TikTok & Instagram) for brand awareness and Marketplaces (Shopee/Tokopedia) for transaction efficiency. Furthermore, successful adaptation requires a transition from "selling" to "educating" consumers about product quality. This study provides a strategic map for livestock SMEs to increase sales volume and market reach through digital technology. The findings also reveal that structural barriers, such as limited digital literacy among older farmers and inadequate cold-chain logistics for perishable products, remain significant obstacles to full-scale adoption. These insights offer practical guidance for SME actors and policymakers seeking to accelerate the digital transformation of the livestock processing industry.